EXPLANATORY GAP AND HARD PROBLEM OF CONSCIOUSNESS ON PHILOSOPHY OF MIND: A CRITICAL STUDY ON SOUL-BODY RELATION POINT OF VIEW IN MULLÂ ŚADRÂ’S PHILOSOPHY - Wa Ode Zainab Zilullah Toresano; Kholid al-Walid (Jurusan Aqidah dan Filsafat Islam Universitas Negri Sunan Gunung Djati Bandung, 2023)
Abstract The goal pf this research to examine Śadrâ’s view on the “soul-body relation” in order to solve the “explanatory gap and the hard problem of consciousness” which are the basic core of the mind-body problem in the philosophy of mind. The explanatory gap explains how physical property can give influence non-physical things conversely. Meanwhile, the hard problem mentions how physical system (material) can produce subjectivity in the mind (non-physics/ immaterial), especially when we have experience. In this context, there is a gap that appears between the immaterial mind and the material body. According to the author’s view, Śadrâ’s philosophy of mind-body relation can solve the problem because it is based on principles of Hikmah Muta’âliyah philosophy, which is “monis of existential-dualism of essential” [in author’s term]. In this research, the author develops the research using Paul Ricoeur’s hermeneutic and philosophical approaches. This research would like to highlight Hikmah Muta’âliyah philosophy, which synthesizes philosophy, theology, and tasawuf (‘irfân), which can be the reference for Muslims (or anyone interested in Islamic Philosophy) to solve philosophical problems. In other explanations, Islamic tradition [in this paper it is represented by Śadrâ] can contribute to contemporary philosophical discourse without making tendentious claim that Western Philosophy cannot solve problems better than the philosophy of Śadrâ.